I, Frankenstein [videorecording (DVD)] - Beattie, Stuart; Eckhart, Aaron; Otto, Miranda; Nighy, Bill, 1949-; Strahovski, Yvonne, 1982-; Courtney, Jai; Otto, Socratis; Grevioux, Kevin; Klimek, Johnny, 1962-; Heil, Reinhold; Emery, Ross; Grevioux, Kevin (Lions Gate Entertainment, 2014)
Set in a dystopic present where vigilant gargoyles and ferocious demons rage in a battle for ultimate power, Victor Frankenstein's creation Adam finds himself caught in the middle as both sides race to discover the secret to his immortality.